Characteristics of the Toba Batak Society from a Cultural Perspective and Its Relevance to the Formation of Character in the Lake Toba Region - Firmando, Harisan Boni (Malikussaleh Social and Political Reviews, 2024)
This research is motivated by the increasingly limited understanding of the various positive characteristics of the Toba Batak society, leading to the emergence of a negative paradigm stating that the Toba Batak people are less friendly and less service-oriented. As a result, the designation of the Lake Toba area as a special region has had limited impact because it has not received support from the community. The purpose of this research is to understand the character of the Toba Batak society from a cultural perspective, which includes the character of family members in the Toba Batak society and efforts to shape the character of the community in the Lake Toba area. This research uses a qualitative method to understand social phenomena. The results show that the family is the smallest social unit that plays a crucial role in character formation. The formation of the community's character in the Lake Toba area has been passed down through generations. Character formation is carried out through private spaces within families as well as in public spaces within the wider community. Character formation in both private and public spaces contributes to the realization of social harmony in the Lake Toba area.